Continuing Multiplication of Salmonella enteritidis Strains in Egg Yolk During Refrigeration at 7.2oC - Gast , Richard K.; Guraya, Rupa (International Journal of Poultry Science, 2013)
The continuing attribution of human illness caused by Salmonella enteritidis to the consumption of contaminated eggs has led to widespread implementation of risk reduction programs for commercial egg production, often emphasizing prompt refrigeration of eggs to prevent bacterial multiplication to dangerously high levels. However, microbial growth may not cease immediately inside warm eggs after transfer to refrigerated storage. The present study compared the abilities of 8 S. enteritidis strains (of 4 phage types) to continue multiplying in experimentally contaminated egg yolk during the first 24 h after transition from warm to refrigeration temperatures. After 15 mL samples of egg yolk were inoculated with 10 CFU/ml of S. enteritidis, they were incubated at 37°C for 16 h and then transferred into refrigeration at 7.2°C for 24 h. Bacterial cell concentrations were determined following 37°C incubation and again after both 8 and 24 h at 7.2°C. All 8 S. enteritidis isolates multiplied significantly during 16 h of incubation, reaching an overall mean of log10 8.790 CFU/ml. After refrigeration, the observed mean values for cell concentrations in yolk samples were log10 8.780 CFU/mL at 8 h and log10 8.849 CFU/mL at 24 h. For 3 of 8 strains, a significant (p